Laser scanner 3d terrestri e mobile - Ciamba, Mario Velio (GEOmedia, 2013)
On the day of May 17, 2012 was held in Rome a demonstration event to inform professionals and researchers regarding the instrumental survey on the recent innovations that affect 3d laser scanner. The market of instrumentation for detecting and architectural environment, offers many choices. Today the major brands produce instruments that are more efficient and designed for specific areas of application, enabling professionals, the right choice in terms of performance and economy.